calcule:
me ajudem pffffffffffffffffffffffffffff
Anexos:
![](https://pt-static.z-dn.net/files/d53/7fe57e4ce1fda399e05e8787f506f628.png)
Soluções para a tarefa
Respondido por
1
5 + 6 = (x + 9) + (x - 3)
11 - 9 + 3 = 2x
2 + 3 = 2x
x = 5 ÷ 2
x = 2,5
5 + 6 = (x + 9) + (x - 3)
11 = (2,5 + 9) + (2,5 - 3)
11 = 11,5 - 0,5
11 = 11
Espero ter ajudado!
11 - 9 + 3 = 2x
2 + 3 = 2x
x = 5 ÷ 2
x = 2,5
5 + 6 = (x + 9) + (x - 3)
11 = (2,5 + 9) + (2,5 - 3)
11 = 11,5 - 0,5
11 = 11
Espero ter ajudado!
Perguntas interessantes